2004
DOI: 10.1016/j.pscychresns.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of cue-induced cigarette craving and anterior cingulate cortex activation in bupropion-treated smokers: a preliminary study

Abstract: In untreated smokers, exposure to cigarette-related cues increases both the intensity of cigarette craving and relative glucose metabolism of the perigenual/ventral anterior cingulate cortex (ACC). Given that treatment with bupropion HCl reduces overall cigarette craving levels in nicotine dependent subjects, we performed a preliminary study of smokers to determine if bupropion HCl treatment attenuates cue-induced cigarette craving and associated brain metabolic activation. Thirtyseven, otherwise healthy smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 77 publications
(96 reference statements)
10
98
3
Order By: Relevance
“…Furthermore, the NON-EXP group had the same cue-related increases in craving as the EXP group and higher average craving reports during the scanning session despite failing to demonstrate any frontal activation to the cues (Table 2). We note, however, that other cue-reactivity imaging studies have uncovered a correlation between craving and ACC activation (Maas et al, 1998; Myrick et al, 2004;Brody et al, 2004;McClernon et al, 2005).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Furthermore, the NON-EXP group had the same cue-related increases in craving as the EXP group and higher average craving reports during the scanning session despite failing to demonstrate any frontal activation to the cues (Table 2). We note, however, that other cue-reactivity imaging studies have uncovered a correlation between craving and ACC activation (Maas et al, 1998; Myrick et al, 2004;Brody et al, 2004;McClernon et al, 2005).…”
Section: Discussionmentioning
confidence: 50%
“…In one, smokers undergoing smoking cessation treatment with the drug bupropion were compared to regular smokers not attempting to quit in a positron emission tomography study employing both visual cues and actual cigarettes (Brody et al, 2004). The untreated smokers had a significantly greater increase in glucose metabolism in the ACC than the bupropion group, when comparing smoking to neutral cues.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the short stimulus duration (5 sec) and brevity of the experiment was not sufficient to induce an increase in tobacco craving. However, regions similar to those activating in our study have demonstrated activation when stimulus duration was sufficient to evoke heightened drug craving (Brody et al 2004a;Garavan et al 2000). Thus, the involvement of reward signaling brain regions in our experiment may represent preconscious processes indicative of heightened incentive salience while our paradigm was not sensitive enough to detect the conscious manifestation of tobacco craving or wanting.…”
Section: Discussionmentioning
confidence: 57%
“…This group of treated subjects had a significant reduction in smoking levels from pre-to post-treatment (mean 27.1 cigs/d pre-treatment to a mean of 3.7 cigs/d post-treatment). Bupropion-treated smokers also had reduced cigarette cue-induced craving and diminished ACC activation when presented with cigarette-related cues, compared to untreated smokers (Brody et al, 2004b). This diminished ACC activation was due to elevated baseline normalized ACC activity in treated smokers, giving an indication that bupropion treatment of smokers increases resting ACC metabolism.…”
Section: Functional Brain Imaging Of Cigarette Cravingmentioning
confidence: 92%